Imunoexpressão de metaloproteinases 2 e 14 e do inibidor TIMP-2 no câncer colorretal - Furtado, Francisco Nélson Nóbrega (2012)
The colorectal cancer (RCC) is highly prevalent in richer and industrialized countries. The matrix metalloproteinases (MMPs) are regarded as important for facilitating tumor invasion and spread in various cancers, including colorectal. Tissue inhibitors of metalloproteinases (TIMPs) are the major physiological inhibitors of MMPs. The expression of metalloproteinase-2 (MMP-2), metalloproteinase 14 (MMP-14) and tissue inhibitor of metalloproteinases-2 ( TIMP-2) in colorectal cancer was assessed. CD68 immunostaininig was utilized to the characterization of mononuclear cells nature. Paraffin-embedded tissues from patients undergoing colectomy for colorectal cancer in the period 2004 to 2010, were selected from the files of the Department of Pathology and Forensic Medicine (DPML), Medical School , Federal University of Ceará (UFC). Tissue microarrays were performed and slides were obtained for immunohistochemical detection of the expression of MMP-2, MMP-14 and TIMP-2 and the tissue samples analyzed. The following scores were applied: 0 = no immunostaining or rare labeled cells (<5%), 1 = slight marking the majority (> 50%) of tumor cells or stromal mononuclear cells, or moderate marking in a minority of cells (<50%) 2 = moderate labeling in the majority (> 50%) of tumor or mononuclear cells or intense marking in the minority of cells (<50%) and 3 = intense labeling in the majority (> 50%) of tumor cells or mononuclear cells. In this study, the relationship between increased expression of MMP-14 in mononuclear primary tumor cells and cases without lymph node metastases (MMP-14, 2 and 3/N0 scores: 23/26 = 88%; N1-N3: 14/21 = 67%, p = 0.0353) was stablished . However, no significant relationship was found between the immunohistochemical expression of MMP-14, MMP-2 and TIMP-2 in primary tumors in cancer cells and mononuclear cells and other clinico-pathological parameters. The expression of MMP-2 were negative in the neoplastic cells both in primary tumors (47/47 = 100%) and in metastatic ones (12/12 = 100%). The immunoreactivity of MMP-14 in neoplastic cells in primary tumors was positive (50/50 = 100%) and in all cases except one of metastatic carcinoma (7/8 = 88%). In mononuclear cells, most of them characterized as macrophages (CD68 stained), MMP-14 positive expression also predominated markedly, both in primary tumors (46/47 = 98%) and in metastatic carcinomas (9/10 = 90%). TIMP-2 expression in neoplastic cells of primary tumors occurred in 35/50 cases (70%) and lymph nodes showed positive immunostaining in all cases (8/8 = 100%). In both sites there were no cases with high expression. The TIMP-2 immunoreactivity in tumour associated macrophages (TAMs) was even higher than in the neoplastic cells. In conclusion, MMP-14 and TIMP-2 are frequently expressed in colorectal carcinomas in both anatomical sites , mainly in lymph node metastasis, suggesting that these proteases play an important role in local invasion and tumor progression of these cancers. The predominance of these biomarkers in mononuclear cells, clearly evident in the positivity for MMP-2, emphasizes the importance of tumor microenvironment in the development of neoplasms.